Malaysia’s Macroeconomic Policies Responses to Commodity Crisis - Hartini Mohammad; Muhammad Imam Bin Azmi; Aisyatul Humairah Binti Salehudin; Amira Nur Izzati Binti Abdul Razak; Nur Alya Nadhirah Binti Azrim Akhtar; Wan Nur Nashra Binti Wan Kamarulsani (Fakulti Ekonomi dan Muamalat, Universiti Sains Islam Malaysia, 2024)
The Oxford Advanced Learner’s Dictionary (1995) defined “crisis” as “a time of great difficulty or danger or when an important decision must be made”. According on the situation, there are many definitions for the term "crisis" in use. It was initially used in the field of medicine to indicate the stage of a disease at which a significant development or change had occurred that was either critical to survival or death. The word "crisis" has, nevertheless, become often used in the 20th century. Five significant crises have been identified to give huge impact on Malaysian economy namely were the "early commodity crisis" between 1956 and 1972, the "first oil crisis" between 1973 and 1974, the "second commodity/oil crisis" between 1980 and 1981, the "electronic/third commodity crisis" between 1985 and 1986, and the "financial and currency crisis" between 1997 and 1998 followed by the 2008 Financial Crisis. Commodity crisis is a crisis that extends from the initial commodity crisis of 1956-72, the first oil crisis of 1973-74, the second commodity or oil crisis of 1980-81 and the third commodity or electronics crisis of 1985-86. Recently, the price of the energy and food has been raising again which can results in the next wave of commodity crisis for the country. The prices of food as a whole had gone up as can be seen in the prices of vegetables and poultry. The global food price index tracked by the Food and Agriculture Organisation of the United Nations showed that in March 2022, it was almost 30 per cent higher year-on-year, hence, result in a really bad food price inflation experienced globally. With reference to energy price, although the world is facing an energy crisis where the demand for energy commodities exceeds supply and this is causing volatility in short-term pricing with global spot prices for natural gas reaching the highest level this year, reports by the government claimed that the impact of the energy crisis on Malaysia has not been alarming. Yet, necessary macroeconomies policies need to be identified to prevent unforeseen impact on the economic growth and society.